ANALISIS PENGENDALIAN KUALITAS UNTUK MENGURANGI PRODUK CACAT MENGGUNAKAN METODE FAILURE MODE AND EFFECT ANALYSIS DAN PROCESS CAPABILITY INDEX PADA PROSES PRODUKSI KEMASAN KALENG (Studi Kasus PT X) - Nadya Permata Sari Putri; Jaka Purnama (JURNAL REKAYASA SISTEM INDUSTRI, 2026)
This study aims to analyze and control the quality of can products by identifying the main causes of defects and evaluating the capability of the production process. The problem faced by the company is the high defect rate exceeding the established standards, particularly dominant defects such as scumming. The methods used in this study are Failure Mode and effect Analysis (FMEA), the Plan-Do-Check-Act (PDCA) cycle, and the process capability index (Cpk). Data were collected through observation, interviews, and documentation during a specific production period. The analysis begins with identifying dominant defects using a Pareto diagram, followed by FMEA to determine the priority of failure causes based on the Risk Priority Number (RPN). Furthermore, continuous improvement is implemented through the PDCA cycle, which includes planning corrective actions, implementation, evaluation, and process standardization. The final stage involves calculating the Cpk index to assess the process capability in meeting company specification limits. The results indicate that several main defect causes with the highest RPN values require immediate improvement. The implementation of PDCA contributes to reducing defect rates and improving process control. However, the obtained Cpk values show that the production process is not yet fully stable and still requires further improvement. Therefore, improvements should focus on critical factors such as machine settings, operator skills, and operational procedures.